Unveiling the Interrelations Between Migration, Climate Change, and Energy Transitions in the Context of Socioeconomic Disparities - Katarzyna Łukaniszyn-Domaszewska; Katarzyna Mazur-Włodarczyk; Marian Łukaniszyn (Energies)
This study examines the critical interplay between migration, climate change, energy transitions, and socioeconomic disparities, highlighting their collective influence on regional resilience and sustainable development. By analyzing the existing literature, the study investigates how migration patterns are shaped by environmental stressors, energy challenges, and economic inequalities, emphasizing the dual role of migration as both a response to and a driver of climate change. Additionally, it explores the complex relationship between energy systems and migration flows, focusing on the impact of energy access, transitions, and sustainability efforts on socioeconomic conditions, particularly in vulnerable regions. The review identifies key gaps in the literature, especially regarding the economic and social implications of these interconnected factors. It also assesses how energy transitions can either mitigate or exacerbate regional disparities and resilience to climate-induced migration. This holistic perspective aims to inform future policy and research on climate migration, energy security, and socioeconomic equity.